2005
DOI: 10.1017/s0265021505000335
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin vs. midazolam premedication in children: a double-blind, placebo-controlled study

Abstract: Melatonin was not only as effective as midazolam in alleviating preoperative anxiety in children, but it was also associated with a tendency towards faster recovery, lower incidence of excitement postoperatively and a lower incidence of sleep disturbance at week 2 postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(116 citation statements)
references
References 38 publications
4
108
3
Order By: Relevance
“…Naguib and Samarkandi [32] found that melatonin (0.5 mg/kg) was associated with preoperative anxiolysis and sedation without impairment of cognitive and psychomotor skills or affecting the quality of recovery. Samarkandi et al [35] reported that 0.25 and 0.5 mg/kg melatonin was not only as effective as midazolam in alleviating preoperative anxiety in children but also associated with a tendency toward faster recovery and lower incidence of excitement postoperatively. Caumo et al [36] reported that patients treated with melatonin preoperatively had a significant decrease in pain and anxiety at all time points assessed during the first 36 h after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Naguib and Samarkandi [32] found that melatonin (0.5 mg/kg) was associated with preoperative anxiolysis and sedation without impairment of cognitive and psychomotor skills or affecting the quality of recovery. Samarkandi et al [35] reported that 0.25 and 0.5 mg/kg melatonin was not only as effective as midazolam in alleviating preoperative anxiety in children but also associated with a tendency toward faster recovery and lower incidence of excitement postoperatively. Caumo et al [36] reported that patients treated with melatonin preoperatively had a significant decrease in pain and anxiety at all time points assessed during the first 36 h after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…29 Melatonin demonstrated beneficial results in children in attenuating emergence agitation following sevoflurane anaesthesia. 30 One of the limitations of the current study is the absence of a placebo-controlled group. It was initially suggested but rejected by the Hospital Ethics Committee.…”
Section: This Article Has Been Retractedmentioning
confidence: 95%
“…88 In the context of pediatric surgery, two clinical trials involving children reported that melatonin was as effective as midazolam in reducing preoperative anxiety. 89,90 In addition, melatonin was associated with a more rapid recovery, a reduced incidence of postoperative delirium, and a lower incidence of sleep disturbances 2 weeks after surgery when compared with midazolam.…”
Section: Surgical Neonates and Childrenmentioning
confidence: 98%